A Case of Burkholderia cepacia Sepsis in a postpartum patient with colonic perforation due to Ogilvie's syndrome: Case from a tertiary care hospital in Bangladesh (Bangladesh Critical Care Journal, 2023)
Traditionally known as a nosocomial organism and preponderance to infect the immunocompromised patients or withpreexisting structural damage in lung parenchyma1, Burkholderia cepacia infection in an apparentlyimmunocompetent host in ICU settings is not very commonly heard of. On the other hand, acute colonicpseudo-obstruction (Ogilvie’s syndrome) is also a very rare surgical complication. Here we present a case of apostpartum lady who developed colonic perforation following caesarean section due to Ogilvie’s syndrome andBurkholderia cepacia sepsis and eventually expired.Bangladesh Crit Care J March 2023; 11 (1): 43-45